FACTORS AFFECTING THE UTILIZATION OF HEALTH SERVICES AMONG DIABETICS IN INDONESIA - Idris, Haerawati; Mursyid, Raja Salsabila (Malaysian Journal of Public Health Medicine, 2023)
Deaths in Indonesia are mostly caused by diabetes mellitus, a non-communicable disease due to a person’s unhealthy lifestyle. The number of health facilities increases annually with the high prevalence of diabetes cases in Indonesia. This study aims to analyze factors affecting the utilization of health services among diabetic people in Indonesia. It was a quantitative study with a cross sectional design, using secondary data of IFLS-5. The theory used was the Andersen’s health service utilization model. A multistage random sampling was used to obtain 534 user data that matched the inclusion and exclusion criteria. Data were analyzed using the chi-square analysis and logistic regression. The results showed that the number of respondents who used inpatient services was 16.9%, and that who used outpatient was 44.4%. The variables that were significantly related to the utilization of inpatient and outpatient health services in diabetic people were socio demographic caracteristic, ownership of health insurance, perception of health status, suffering from chronic diseases and daily activities. It is important for policymakers in the health sector must improve financial or economic access to health services, as well as health service equity in all regions.